Kenyan farmers in Kisumu and Vihiga are embracing nature-positive agri-food systems - Kinuthia, Dickson; Boukaka, Sedi Anne; Davis, Kristin E.; Zhang, Wei; Hettiarachchi, Upeksha (CGIAR System Organization, 2024)
Nature-positive solutions are practices that sustainably provide food and livelihoods for farmers while ensuring that agriculture is a net positive contributor to biodiversity and nature. In Kenya, the CGIAR Nature-Positive Solutions (NATURE+) Initiative is working with farmers to implement these practices, especially through NATURE+ farms, where farmers come together to implement nature-positive solutions, which are being designed in Kisumu and Vihiga Counties.